2018
DOI: 10.1080/1331677x.2018.1438906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of institutional quality on foreign direct investment inflows: evidence for developed and developing countries

Abstract: This study examines the impact of institutional quality on foreign direct investment (F.D.I.) by categorising the countries as developed or developing. We measured institutional quality by the sum of control of corruption and rule of law indicators. We provide evidence that institutional quality positively and significantly impacts F.D.I. in developed countries; specifically, we find that a one standard deviation change in governance significantly affects F.D.I. by a factor of 0.2225 (using common law and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
97
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 65 publications
(87 reference statements)
13
97
1
1
Order By: Relevance
“…Some countries tend to decrease the control of corruption in the crisis period. This was noticeable among developing countries including Croatia, which proved to be the post-transition country with the most negative changes in control of corruption and the rule of law during the last crisis (Peres et al, 2018). Also, according to UNCTAD (2018), Croatia had four new investor-state dispute settlement claims in 2017, which made her the most frequent respondent in this field in the world for the mentioned year.…”
Section: Introductionmentioning
confidence: 99%
“…Some countries tend to decrease the control of corruption in the crisis period. This was noticeable among developing countries including Croatia, which proved to be the post-transition country with the most negative changes in control of corruption and the rule of law during the last crisis (Peres et al, 2018). Also, according to UNCTAD (2018), Croatia had four new investor-state dispute settlement claims in 2017, which made her the most frequent respondent in this field in the world for the mentioned year.…”
Section: Introductionmentioning
confidence: 99%
“…Corruption is one of the institutional qualities that can determine FDI inflows in a country. Studies have shown that countries with good regulatory framework attract more FDI inflows while those with poor legal structure cannot safeguard investment (Peres, Ameer & Xu, 2018) and so foreign investors are scared of investing in such countries. Corruption includes bribery and any other activities of people, having obligation in the public or private sector, who disrupt their responsibilities for selfish gains (Gasanova, Medvedev & Komotskiy, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…dynamics in ex-transitional economies (nowadays some of them are E.U. members and emerging European countries) are investigated by various authors (e.g., Peres et al, 2018;Sondermann & Vansteenkiste, 2019). The research could be classified into three groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The question what are the main motives that drive F.D.I., is mostly occupying the attention of the researchers in economic literature. It is the subject of numerous theoretical and empirical researches (e.g., A sanin Gole, Ma cek, & Vukasovi c, 2016;Popescua, 2013;Makuyana & Odhiambo, 2018;Peres, Ameer, & Xu, 2018;Kamal, Ullah, Zheng, Zheng, & Xia, 2019;Pietrucha & Zelazny, 2019;Jia, Han, Peng, & Lei, 2019). But on the other side, economic literature does not provide enough research on the topic of regulatory framework and F.D.I.…”
Section: Introductionmentioning
confidence: 99%